2011
DOI: 10.1007/s10811-011-9698-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic tetrapyrrolic photosensitizers from Cladophora patentiramea (Cladophoraceae, Chlorophyta) and Turbinaria conoides (Sargassaceae, Phaeophyta) for photodynamic therapy

Abstract: In screening for novel photosensitizers for photodynamic therapy, 14 seaweed samples from Port Dickson in Malaysia were collected. Methanolic extracts of these samples were prepared and evaluated for phototoxicity using a short-term cell viability assay, where promyelocytic leukemia cells, HL60 were incubated with the extracts prior to irradiation with a broad spectrum light at 9.6 Jcm −2 (equivalent to 10.5 mW cm −2 for 10 min). Four of the methanolic extracts demonstrated moderate to strong phototoxicity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…473 Included in the green algal literature for 2012 were a number of papers, that while not reporting new compounds, are worthy of comment. These include the nding that separate isoprenoid-24-alkyl sterol pathways have evolved in fungi and green algae which converge to yield ergosterol, 474 the role of caulerpin as a potential antiviral drug against HSV Type 1, 475 tetrapyrrolic pigments as photosensitisers for photodynamic therapy 476 and a careful evaluation of the antioxidant activity of a wide range of Hawaiian brown, red and green algae. 477 Also of interest was the identication of 208 volatile compounds from the green alga, Capsosiphon fulvescens, used by Koreans for centuries for its unique taste and avour properties.…”
Section: Green Algaementioning
confidence: 99%
“…473 Included in the green algal literature for 2012 were a number of papers, that while not reporting new compounds, are worthy of comment. These include the nding that separate isoprenoid-24-alkyl sterol pathways have evolved in fungi and green algae which converge to yield ergosterol, 474 the role of caulerpin as a potential antiviral drug against HSV Type 1, 475 tetrapyrrolic pigments as photosensitisers for photodynamic therapy 476 and a careful evaluation of the antioxidant activity of a wide range of Hawaiian brown, red and green algae. 477 Also of interest was the identication of 208 volatile compounds from the green alga, Capsosiphon fulvescens, used by Koreans for centuries for its unique taste and avour properties.…”
Section: Green Algaementioning
confidence: 99%
“…Cladophora patentiramea (Montagne) K€ utz. is a potential source of new types of cyclic tetrapyrrolic photosensitizers for photodynamic therapy (Tang et al 2012). Such applications may be more economically feasible than utilizing Cladophora biomass in anaerobic digesters.…”
Section: Ecosystemsmentioning
confidence: 99%
“…Drugs targeting phosphatases are considered as promising novel cancer therapies. Recently, 36 Tang et al, (2012) isolated some cyclic tetrapyrrolic photosensitizers from C. patentiramea and demonstrated that they exhibit important photo toxicity against HL60 promyelocytic leukemia cells. To date, a number of photosensitizers derived from natural products have been clinically approved for the photo dynamic therapy of specific cancers (37).…”
Section: Discussionmentioning
confidence: 99%